Online conferencing for focus group discussions with teenage girls. (24th July 2019) - Thompson, Roberta
Abstract : Purpose: The purpose of this paper is to examine the use of online conferencing platforms for focus group discussions with teenage girls. Design/methodology/approach: The paper discusses the use of online conferencing for focus group discussions with Australian teenage girls aged 12–14 years who were participating in a study about their online interaction with friends. It examines both the practical application of online conferencing as a qualitative method as well as the inherent challenges of this context for youth research. Design decisions are explained and methods for ensuring rich contribution are detailed. Findings: Online conferencing offers three distinct advantages for focus group work. First, the environment consciously engages participants in spontaneous interaction with other participants by using communication tools familiar to them. Second, elaborated discussion can be stimulated by introducing ideas and trends through visual mediums and artefacts. Third, the virtual setting provides remote access by the researcher which shifts power relationships so discussions flow more naturally between participants. Practical implications: Outcomes indicate that online conferencing is an effective method for encouraging participants to share ideas and experiences about aspects of their lives that are often private and/or sensitive. Originality/value: Technological advances in online collaboration tools have resulted in an increased use of online conferencing platforms across disciplines especially for teaching and learning contexts. However, application of online conferencing for focus group discussions with young people has not received much attention. Research presented here demonstrates that it is a useful tool for engaging teenage girls in focus group discussions.